LIMNO-BIOLOGI PERAIRAN MUSI BAGIAN HULU DI PROVINSI BENGKULU DAN SUMATERA SELATAN - Samuel, Samuel; Nurul Aida, Siti (Faculty Fisheries Departement Fisheries, 2004)
Study on limno-biological aspect of the upper part of Musi river Basin was conducted in June, September, and December 1997. The objective of this study was to find out the characteristics of limno-biology of the upper Musi river as important factors for fishery management in the catchment area. Purposive sampling method by selecting 3 (three) research stations was applied in this study. Result showed that the range of water quality value such as temperature, water current, pH, dissolve oxygen, carbondioxide, alkalinity, hardness, conductivity varied in the range of 23-28Â°C, 0,40-0,80 m/second, 7,3-8,0 units, 8,26-10,58 mg/L, 3,09-6,18 mg/L, 33,62 mg/L, 60-112 mg/L and 28-43 umhos/cm, respectively. The abundance of benthic organism varied from 24 to 69 individu/m2 consisting of insect, gastropoda, amphiphoda and nematode. Drift organism were consisted of 5 groups i.e phytoplankton, zooplankton, fragment of insecta, crustaceae and plant fragments. Thirthy eight species derived from 11 families were caught during the study. There was abundancy tha their distribution was affected by the altitude. The number fish species was descreasing with increasing in the altitudes.Keywords: limno-biology, upper part of Musi river, fisheries management